The Concept of Useful Knowledge in Hadith and its Implications for Contemporary Islamic Education - Muhammad Hizba Aulia; Elan Sumarna; Cucu Surahman; Aufa Assa Syahada (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
Islamic education aims to instil helpful knowledge, with the obligation to convey knowledge as a primary indicator. In today's digital era, while the dissemination of knowledge has become more widespread, its intensity and the quality of the knowledge shared often do not compare to that of the past. This study examines how the principle of knowledge dissemination, as emphasized in Islamic teachings, can be effectively applied in contemporary Islamic education to address these challenges. Employing a qualitative approach with content analysis, the study analyzes primary sources, including the hadith text Sahih Bukhari No. 65 and secondary sources, such as Fathul Bari Syarah Sahih Bukhari, journal articles, and other relevant literature. The data were analyzed by identifying the values within the hadith and linking them to modern educational practices, including learning technologies and teaching methods. The findings indicate that education emphasizing the dissemination of beneficial knowledge can enrich the learning experience and enhance teaching quality. The application of methods such as recitation, active learning, and the use of digital technology supports this principle. In conclusion, Islamic education must integrate these values to create an environment that focuses on mastery of knowledge and applying moral values in daily life.